Digital Transformation And Its Impacts on Sustainable Competitive Advantage: The Moderating Role of Entrepreneurial Innovation - Donant Alananto Iskandar; Triyono Arief Wahyudi; Fakhrorazi bin Ahmad (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
This research aims to analyze the effect of dynamic capabilities and market opportunities towards digital innovation and analyze the moderating effect of technological disruption towards the influence of dynamic capabilities and market opportunities on digital innovation. This research will be conducted as quantitative research. The questionnaire will be developed to measure all of the variables and will be distributed to the senior staff of the digital business companies. Four hypotheses will be tested. This research will contribute to the empirical evidence of the effect of dynamic capabilities and market opportunities towards digital innovation and analyze the moderating effect of technological disruption on the influence of dynamic capabilities and market opportunities on digital innovation